Gobernanza y territorios indígenas. Cambios, permanencias y redefiniciones - Chirif, Alberto (2022)
This article deals with the social and economic processes that led to creating an institution known as “native community”, formally in 1974 through a specific law. Furthermore, we deal here with the attempts by various administrations to undermine it. We also explain the criteria underpinning traditional indigenous governance and the important role of communities, organized as second level organizations, have played in specific contexts (demands claiming rights’ violations, legal and political proposals, the country’s pacification and ways of dealing with Covid-19). Finally, the article examines the emergence of a new subject of rights, namely “indigenous people”, who are also the bearers of other rights such as the right to an integrated territory and autonomous governance-that are still in the making.